2013
DOI: 10.1002/adma.201204509
|View full text |Cite
|
Sign up to set email alerts
|

Gas Dielectric Transistor of CuPc Single Crystalline Nanowire for SO2 Detection Down to Sub‐ppm Levels at Room Temperature

Abstract: Sulfur dioxide (SO 2 ) is one of the most dangerous air pollutants that impair environment and human health. SO 2 in air is released during the burning of fossil fuels and plays one major role in the formation of acid rain. The repeated exposure to low levels of SO 2 can cause permanent pulmonary impairment for humans. [ 1 ] The long and short-term exposure limits for SO 2 gas are 2 and 5 ppm, respectively, [ 1 , 2 ] and the U. S. Environmental Control Agency has set the acceptable limit for SO 2 in ambient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
136
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(140 citation statements)
references
References 28 publications
1
136
0
3
Order By: Relevance
“…Shaymurat et al reported OFET based on CuPc single crystalline nanowire as a novel SO 2 sensor which the detect limitation is down to sub-ppm levels. 4 Miyata et al prepared MPc thin films Cl 2 gas sensor using vacuum deposition, and Cl 2 with a minimum concentration of 0.18 ppm could be detected in the operating temperature range from 25 to 200 • C. 13 In this paper, we demonstrated template-free preparation and device integration of singlecrystalline CuPc nano column for room temperature Cl 2 detecting at ppb level. The rectangular section CuPc nano column can be controlled and grown on quartz, glass, sapphire, silicon and SiO 2 /Si substrates, proving that the aligned growth of nano columns is not substrate-dependent.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Shaymurat et al reported OFET based on CuPc single crystalline nanowire as a novel SO 2 sensor which the detect limitation is down to sub-ppm levels. 4 Miyata et al prepared MPc thin films Cl 2 gas sensor using vacuum deposition, and Cl 2 with a minimum concentration of 0.18 ppm could be detected in the operating temperature range from 25 to 200 • C. 13 In this paper, we demonstrated template-free preparation and device integration of singlecrystalline CuPc nano column for room temperature Cl 2 detecting at ppb level. The rectangular section CuPc nano column can be controlled and grown on quartz, glass, sapphire, silicon and SiO 2 /Si substrates, proving that the aligned growth of nano columns is not substrate-dependent.…”
Section: Introductionmentioning
confidence: 83%
“…3,4 Geohegan group has prepared high-quality single-crystalline nanowires with good control over the wire structure and morphology, and exploited organic field-effect transistors (OFETs) based on individual α-phase nanowires, which exhibits excellent performance. 5 Jie et al developed simultaneous patterned growth and device integration of cross-aligned single-crystalline organic nanowire arrays for optical image sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[78][79][80][81][82][83][84][85][86] Owing to the intrinsic merits of CPs and OSCs, such as their tremendous variety with regard to molecular engineering, light weight, low cost, mechanical flexibility, and room-temperature operation capability, etc., most of the disadvantages of inorganic semiconductors-based sensor could be avoided, rendering the CPs-or OSCs-based counterparts promising alternatives. [1,15,87] Nevertheless, most of the investigations focus on gas sensors, wherein thin films of CPs or OSCs are used as active layer. [79,80] Most of these publications use thick active films with a response/recovery time of several minutes to dozens of minutes, preventing them from in situ sensing applications.…”
Section: How To Improve the Performance Of Sensors Through Nanoassembmentioning
confidence: 99%
“…26 Despite of the OSC/electrodes interface, the dielectric/ OSC interface is also crucial to the device performance as the trap sites at dielectric/OSC interface will significantly influence the charge transport, leading to the reduction of channel current and field-effect mobility. 27,28 The trap density (N SS ) presents the density of trap sites and is proportional to subthreshold slope (SS) as shown in Eq. (1) 29…”
mentioning
confidence: 99%